Evaluation of Greenmass Yield of Some Soybean Varieties by Ammi Analysis Method - YAŞAR, Mustafa; SEZGİN, Mehmet (ISPEC Journal of Agricultural Sciences, 2023)
This study was carried out with 4 soybean varieties in four different locations (Adana, Antalya, Manisa, Samsun) according to the Randomized Complete Block Design with six replications. In the study, the variation of greenmass yield of genotypes according to locations was evaluated with AMMI (Additive Main Effects and Multiplicative Interactions) analysis model. According to the analysis of variance genotype, environment, genotype×interaction and PC1 were found to be statistically significant. The greenmass yield for locations varied between 3064-5482 kg da-1, the highest yield was obtained from Adana location, and the lowest yield was obtained from Samsun location. The greenmass yield of the varieties varied between 3918-4520 kg da-1, the highest yield was obtained from 1530 (Yemsoy) variety and the lowest yield was obtained from Türksoy variety. In the AMMI analysis, PC1 accounted for 77.11% of the variation. According to the results obtained with the AMMI analysis, it was determined that the variety 1530 (Yemsoy) had the highest yield in the average of all four locations, while the Nazlıcan variety was above the average (vertical) curve and had high values. The variety 1530 (Yemsoy) was the most stable and the varieties 517 (Yeşilsoy) and Türksoy were far from the stability (horizontal) curve. Three locations, except Manisa location, are located in the same Mega-environment.